Photochemical oxidation of alcohols to ketones or aldehydes using DMSO as an oxidant without activated agent. (26th January 2023) - Zhao, Jinwu; Luo, Zhigao; Liu, Yipeng; Xu, Jingxiu; Huang, Zunnan; Xiong, Wenfang
Abstract: We report visible light mediated oxidation of alcohols to ketones or aldehydes catalyzed by anthraquinone under irradiation at 430–440 nm at room temperature, using DMSO as an oxidant without activated agent. Key parameters, including irradiating wave-length, reaction medium and photocatalyst, are investigated. According this procedure, a variety of alcohols are oxidized to the corresponding ketones or aldehydes in satisfactory yields. This protocol features transition metal free and mild reaction conditions. Graphical abstract: Image 1